Outcomes of SARS-CoV-2 infection in cancer versus non-cancer-patients: a population-based study in northeastern Italy. Issue 1 (February 2023) - Rugge, Massimo; Zorzi, Manuel; Guzzinati, Stefano; Stocco, Carmen; Avossa, Francesco; Del Zotto, Stefania; Clagnan, Elena; Bricca, Ludovica; Dal Maso, Luigino; Serraino, Diego
Introduction: This study assesses the risk of infection and clinical outcomes in a large consecutive population of cancer and non-cancer patients tested for SARS-CoV-2 status. Methods: Study patients underwent SARS-CoV-2 molecular-testing between 22 February 2020 and 31 July 2020, and were found infected (CoV2+ ve ) or uninfected. History of malignancy was obtained from regional population-based cancer registries. Cancer-patients were distinguished by time between cancer diagnosis and SARS-CoV-2 testing (<12/⩾12 months). Comorbidities, hospitalization, and death at 15 September 2020 were retrieved from regional population-based databases. The impact of cancer history on SARS-CoV-2 infection and clinical outcomes was calculated by fitting a multivariable logistic regression model, adjusting for sex, age, and comorbidities. Results: Among 552, 362 individuals tested for SARS-CoV-2, 55, 206 (10.0%) were cancer-patients and 22, 564 (4.1%) tested CoV2+ ve . Irrespective of time since cancer diagnosis, SARS-CoV-2 infection was significantly lower among cancer patients (1, 787; 3.2%) than non-cancer individuals (20, 777; 4.2% - Odds Ratio (OR)=0.60; 0.57-0.63). CoV2+ ve cancer-patients were older than non-cancer individuals (median age: 77 versus 57 years; p<0.0001), were more frequently men and with comorbidities. Hospitalizations (39.9% versus 22.5%; OR=1.61; 1.44-1.80) and deaths (24.3% versus 9.7%; OR=1.51; 1.32-1.72) were more frequent in cancer-patients. CoV2+ ve cancer-patients were at higher risk of death (lung OR=2.90; 1.58-5.24, blood OR=2.73; 1.88-3.93, breast OR=1.77; 1.32-2.35). Conclusions: The risks of hospitalization and death are significantly higher in CoV2+ ve individuals with past or present cancer (particularly malignancies of the lung, hematologic or breast) than in those with no history of cancer.